International Migration and "the New Berlin Walls" (Journal of the College of Education for Women, 2025)
The refugee crisis and the increasing of the international migration towards the developed countries represented by the European Union, the United States of America and Australia have created many problems and the reappearing walls again after 30 years since of the most famous wall collapse in the last century, i.e. the fall of Berlin Wall separating East Germany, West Germany. This research discusses the viewpoints in which different opinions support and oppose building walls by reviewing viewpoints and identifying motivations and reasons for both parties and assessing the effectiveness of border walls by analyzing concerns for illegal immigration.The effectiveness of legitimacy and its future consequences, historical studies have shown that the walls were constructed earlier limited, it has proven to be a complete failure, along with the ideology that supported those walls, and shows limited effectiveness. The walls are currently in place because of the many illegal immigration methods used by smugglers in finding routes and new possibilities for smuggling despite the technical and technological development of border control by developed countries. As, the research is based on the events that the world is witnessing today, including climate change and conflicts over water energy and other resources, this will lead to an increase in the volume of migration and greater displacement to low-lying countries and average incomes in the coming years, which will double the challenges of managing borders